Penguatan Pangan Lokal Berkelanjutan Melalui Edukasi Dapur Sehat Atasi Stunting Bagi Keluarga Berisiko - Binaridha Kusuma Ningtyas; Hidayah Murtiyaningsih; Laras Sekar Arum (Indonesian Journal Publisher, 2023)
Stunting has become a severe problem and has become a global issue. The condition of stunting is malnutrition which can hamper the physical development and intelligence of children, so that it will impact the quality of life in the future. Resolving stunting takes a very long time. It requires changes in behaviour, mindset, and strong political commitment from stakeholders. Understanding stunting is not only a health issue, but also covers a broader aspect. Stunting is a multidimensional issue closely related to social, economic, and educational inequality. The government has carried out many programs or policies to deal with stunting, significantly strengthening assistants or cadres at the village level. This effort aims to provide education and assistance in handling stunting, especially for prospective brides, pregnant women, nursing mothers, and toddlers. In addition to strengthening assistants in the field, the community can support the Dapur Sehat Atasi Stunting (DASHAT) institution. DASHAT is a community participation-based program to encourage balanced nutrition for families at risk of stunting by strengthening local food sources. Community service activities occur in Suci Village, Panti District, Jember Regency. Community service activities are carried out with DASHAT education and assistance by encouraging the strengthening of local food for families at risk of stunting. This activity uses a people-driven centre approach. Through this approach, participants identify and develop local food-based menus that can be used to fulfil balanced nutrition to overcome stunting. This activity can explain to at-risk families that if appropriately processed, local food sources can produce nutritious food.